2017
DOI: 10.1111/anec.12493
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of wide QRS complex tachycardia criteria and algorithms in patients with ventricular preexcitation

Abstract: There are sufficient electrocardiographical differences between VT and preexcited SVT to allow electrocardiographic differentiation. VT score, Steurer algorithm, and some single criteria do not overdiagnose VT in patients with preexcitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
0
17
0
3
Order By: Relevance
“…Antidromic AV reentrant tachycardia will produce a WQRST, but the QRS morphology will depend on the location of the accessory pathway along the AV ring and its ventricular insertion site. The QRS morphology will resemble the morphology of the delta wave observed during sinus rhythm as the ventricle is pre‐excited by the accessory pathway bypassing the AV node and His‐Purkinje system 37,38 …”
Section: Pre‐excited Tachyc Ardiamentioning
confidence: 99%
“…Antidromic AV reentrant tachycardia will produce a WQRST, but the QRS morphology will depend on the location of the accessory pathway along the AV ring and its ventricular insertion site. The QRS morphology will resemble the morphology of the delta wave observed during sinus rhythm as the ventricle is pre‐excited by the accessory pathway bypassing the AV node and His‐Purkinje system 37,38 …”
Section: Pre‐excited Tachyc Ardiamentioning
confidence: 99%
“…However, during provoked or spontaneous maximal preexcitation, ventricular activation accomplished almost exclusively by the AP is observed, with the QRS morphology almost completely depending on the AP location (FIgUrE 1). 8 Variability in the degree of preexcitation in the QRS morphology can explain the difficulty whAt's new?…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…10,16 All from this analysis were found to have a sensitivity of 75% and specificity of 100% and the algorithm was validated in another study but experience is still limited. 18,19 Several independent studies have found that various ECG-based methods have specificities of 40-80% and accuracies of ~75%. 2,10,[19][20][21][22] A similar diagnostic accuracy of ~75% would be achieved effortlessly by considering every wide QRS tachycardia to be a VT because only 25-30% are SVTs.…”
Section: Rs Interval In the Precordial Leadsmentioning
confidence: 99%
“…18,19 Several independent studies have found that various ECG-based methods have specificities of 40-80% and accuracies of ~75%. 2,10,[19][20][21][22] A similar diagnostic accuracy of ~75% would be achieved effortlessly by considering every wide QRS tachycardia to be a VT because only 25-30% are SVTs. Emerging approaches to integrate these algorithms to provide more accurate scoring systems are being evaluated.…”
Section: Rs Interval In the Precordial Leadsmentioning
confidence: 99%